2002
DOI: 10.1258/095646202760029868
|View full text |Cite
|
Sign up to set email alerts
|

Standards for comprehensive sexual health services for young people under 25 years

Abstract: This document is a first response to the need to develop sexual health services for young people on a single site whilst awaiting research from pilot studies of 'one stop shops' suggested in the Sexual Health and HIV strategy. It is a document which is intended to be a tool to use for those wishing to set up a service providing testing for sexually transmitted infections and provision of contraceptive services for those under 25 years. It is not intended that such a service would replace existing specialist or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…43 Only one of the lower-quality studies, the evaluation of the Massachusetts Condom Availability Program, reported a statistically significant result in relation to recent sexual activity, which was lower in the intervention group than the control group. 58 Of the studies which only reported lifetime, not recent, sexual activity, the higher-quality Brazilian evaluation reported slightly higher increases over time in the intervention group than in the control group in the proportion of both male and female students who had ever had sexual intercourse, but these differences were not said to be statistically significant 50 (for details, see Appendix 2, Table 28). Only two of the lowerquality studies reported results that they identified as statistically significant.…”
Section: Impact Of Service Provision On Rates Of Sexual Activitymentioning
confidence: 98%
See 4 more Smart Citations
“…43 Only one of the lower-quality studies, the evaluation of the Massachusetts Condom Availability Program, reported a statistically significant result in relation to recent sexual activity, which was lower in the intervention group than the control group. 58 Of the studies which only reported lifetime, not recent, sexual activity, the higher-quality Brazilian evaluation reported slightly higher increases over time in the intervention group than in the control group in the proportion of both male and female students who had ever had sexual intercourse, but these differences were not said to be statistically significant 50 (for details, see Appendix 2, Table 28). Only two of the lowerquality studies reported results that they identified as statistically significant.…”
Section: Impact Of Service Provision On Rates Of Sexual Activitymentioning
confidence: 98%
“…58 For details of the individual projects, see Appendix 2, Table 26. More general information on the nature of the services represented by the projects is included in Appendix 3.…”
Section: Relevance To Current Uk Service Provisionmentioning
confidence: 99%
See 3 more Smart Citations